2005
DOI: 10.1540/jsmr.41.195
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the involvement of the cyclooxygenase-metabolic pathway in diclofenac-induced inhibition of spontaneous contraction of rat portal vein smooth muscle cells

Abstract: The effects of diclofenac, a cyclooxygenase (COX) inhibitor, were investigated on spontaneous phasic contractions of longitudinal preparations of the rat portal vein. Diclofenac produced a concentration-dependent decrease in the amplitude of these spontaneous phasic contractions. Diclofenac (30 µM) decreased the amplitude of the spontaneous phasic increase in the F340/F380 ratio of Fura PE3, an indicator of intracellular Ca 2+ concentration. It also reduced the number of action potentials in each burst dischar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…This finding was not considered unusual as a similar effect was evident when rat portal veins were exposed to diclofenac (Shimamura et al, 2005). Although the finding is contradictory to glomerular arterial physiology in mammals, it can be explained by finding of Peredo (2003) who demonstrated that indomethacin decreased mesenteric vasoconstriction by inhibiting contractile PGf 2 α production via cyclo-oxygenase (COX) inhibition (Peredo, 2003).…”
Section: Discussionmentioning
confidence: 81%
“…This finding was not considered unusual as a similar effect was evident when rat portal veins were exposed to diclofenac (Shimamura et al, 2005). Although the finding is contradictory to glomerular arterial physiology in mammals, it can be explained by finding of Peredo (2003) who demonstrated that indomethacin decreased mesenteric vasoconstriction by inhibiting contractile PGf 2 α production via cyclo-oxygenase (COX) inhibition (Peredo, 2003).…”
Section: Discussionmentioning
confidence: 81%
“…Arachidonic acid (AA) is metabolized by the vascular endothelium and smooth muscle cells to a variety of cyclooxygenase (COX), lipoxygenase (LOX), and cytochrome P-450 (CYP450) epoxygenase products, and these metabolites exert influences over vascular tone (Sekiguchi et al, 1998;Roman et al, 2000;Roman, 2002;Fleming, 2001;Miyata and Roman, 2005;Shimamura et al, 2005;Vizoili et al, 2005;Imig, 2006). The identity and potential biological activity of some of the relevant AA metabolites remain poorly characterized (structurally and/or biologically).…”
Section: Introductionmentioning
confidence: 99%
“…Although only a proportion of the smooth muscle cells studied showed a response to L-arginine, the depolarization or inward current induced by Larginine may spread over the tissue via cell-to-cell electrical coupling. In rat portal vein using lucifer yellow, we observed that intercellular communication is present (Shimamura et al, 2005).…”
Section: Discussionmentioning
confidence: 85%